Self-healthcare Innovation for the Elderly with Thai Traditional Medicine in the Area of Mae Khao Tom Subdistrict, Mueang Chiang Rai District, Chiang Rai Province - Chaiwong, Nissara; Kaewjantha, Suwanan; Wiriya, Suthida; Mama, Rusanee; Kamsua, Panyarach (Journal of health and health management, 2026)
The objective of this participatory action research was to develop self-healthcare innovations for the elderly with Thai traditional medicine in the area of Mae Khao Tom Sub-district, Mueang Chiang Rai District, Chiang Rai Province, which is a suburban community with potential for local wisdom in healthcare but lacks a systematic model of promoting self-healthcare. The samples were 60 elderly individuals selected by purposive sampling. The research was conducted in four stages: 1) the planning stage by studying health problems and needs of the elderly and community potential; 2) the operational stage by developing innovations through a participatory process; 3) the observation stage; and 4) the reflection stage, conducted in parallel with applying the developed innovations to the sample group with pre- and post-tests administered. Data collection tools included 1) a health problem survey, 2) pre- and post-tests, and 3) satisfaction assessments. Content validity was verified by five experts with an IOC value between 0.60-1.00. Data were analyzed using descriptive statistics including percentage, mean, standard deviation, and inferential statistics with a paired t-test. The results revealed that: 1) the elderly in Mae Khao Tom Sub-district faced health problems with a group of diseases treatable by Thai traditional medicine, and most valued and preferred using Thai herbs and wisdom in healthcare; 2) the community had a role and potential to develop self-healthcare innovations with Thai traditional medicine; 3) two innovations were developed: 3.1) a mobile Thai traditional medicine elderly clinic, and 3.2) a health promotion and prevention activity titled “4S: Longevity Health for the Elderly”; and 4) after using the innovations, the elderly scored significantly higher on self-healthcare knowledge than before at the 0.05 level (t = 21.53), showed improved self-healthcare behaviors, and could apply herbal knowledge in daily life. Overall, 93 percent of the elderly expressed the highest level of satisfaction with the innovations in all aspects.